The Effect Of Increasing Concentrations Of Sodium Saccharin As Sweetener On Physical Properties Of Salbutamol Dispersible Tablet With Mannitol As Filler - Inding Gusmayadi; Pramulani Mulya Lestari; Citra Martalova (Ad-Dawaa : Journal of Pharmacy, 2023)
Salbutamol one of asthma medicine which can be made in to dispersible tablet with the addition of sodium saccharin as sweetener. This study aimed to determine effect of increasing concentration of sodium saccharin as sweetener on physical properties and patient acceptabelity of the tablet. The tablet was made into 5 formulas with the 0% of sodium saccharin concentration as Formula 1, 0.2% as Formula 2, 0.4% as Formula 3, 0.6% as Formula 4, and 0.8% as Formula 5. The tablet made by direct compression method. The evaluation of granule including flow time test, angle of repose, and compressibility test. The tablet evaluation including organoleptic, weight uniformity, size uniformity, friability, hardness, wetting time, disintegration time, content uniformity, and hedonic test. The results of the physial properties were the hardness F1 until F5 subsequently 1.70, 1.54, 2.48, 2.67, and 2.73 Kp; the disintegration time F1 until F5 subsquently 55.67, 56.67, 56.67, 57.00, and 58.00 seconds; the friability test 1.09, 1.98, 0.77, 0.65, and 0.63%. The results showed that there were significant differences among all the formulas. It could be concluded that increasing concentration of sodium saccharin as sweetener in salbutamol dispersible tablet increase physical properties and could be made as preferable and acceptable tablet.